Improving deep RVFL neural networks on large datasets - Li, Bing (Nanyang Technological University, 2021)
Recently, neural networks algorithm is becoming popular among researchers for classification problems such as Handwritten Character Recognition. Gradient descend is a kind of popular method which usually used in neural networks. However, such iteration methods usually lead to train the network slowly. Besides, overfitting the training data is also a problem of this approach. As such, researchers studied the randomised neural networks such as Random Vector Functional Link (RVFL) neural networks and Extreme Learning Machine (ELM) which significantly reduce training time and yet produce good classification performance. ELM neural network is a kind of simplified RVFL neural network. Compared with RVFL, it does not contain the direct link and bias between the input layer and output layer.